IMPLEMENTASI METODE LITERASI DAN RESITASI TINGKATKAN CRITICAL THINKING PESERTA DIDIK - Muzaro’ah Muzaro’ah (Pusat Riset dan Inovasi Nasional, 2023)
Critical thinking is a process of solving problems based on good judgment and experiences that are by facts. A thought process of solving problems in learning is said to be achieved and can improve critical thinking skills in solving problems during the learning process if the implementation is student-centered. To improve critical thinking skills, improve the quality of education, and produce quality learning outcomes, the government made a breakthrough by holding the School Literacy Movement (GLS) program. Namely a mass movement to foster a love of literacy to meet the need for information and reading for this nation's generation. Literacy is the ability of individuals to read, write, speak, calculate and solve problems at the level of expertise required in work, family, and society. Good literacy and followed up by giving assignments or recitations, can hone skills to make students able to think critically, creatively, innovatively and develop student character.